Physical activity is associated with increased resting‐state functional connectivity in networks predictive of cognitive decline in clinically unimpaired older adults. Issue 1 (7th July 2022) - Pruzin, Jeremy J.; Klein, Hannah; Rabin, Jennifer S.; Schultz, Aaron P.; Kirn, Dylan R.; Yang, Hyun‐Sik; Buckley, Rachel F.; Scott, Mathew R.; Properzi, Michael; Rentz, Dorene M.; Johnson, Keith A.; Sperling, Reisa A.; et al.
Abstract: Introduction: Physical activity (PA) promotes resilience with respect to cognitive decline, although the underlying mechanisms are not well understood. We examined the associations between objectively measured PA and resting‐state functional connectivity magnetic resonance imaging (rs‐fcMRI) across seven anatomically distributed neural networks. Methods: rs‐fcMRI, amyloid beta (Aβ) positron emission tomography (PET), PA (steps/day × 1 week), and longitudinal cognitive (Preclinical Alzheimer's Cognitive Composite) data from 167 cognitively unimpaired adults (ages 63 to 90) were used. We used linear and linear mixed‐effects regression models to examine the associations between baseline PA and baseline network connectivity and between PA, network connectivity, and longitudinal cognitive performance. Results: Higher PA was associated selectively with greater connectivity in three networks previously associated with cognitive decline (default, salience, left control). This association with network connectivity accounted for a modest portion of PA's effects on Aβ‐related cognitive decline. Discussion: Although other mechanisms are likely present, PA may promote resilience with respect to Aß‐related cognitive decline, partly by increasing connectivity in a subset of cognitive networks.